Comprehensive vascular imaging using optical coherence tomography-based angiography and photoacoustic tomography - Zabihian, Behrooz; Chen, Zhe; Rank, Elisabet; Sinz, Christoph; Bonesi, Marco; Sattmann, Harald; Ensher, Jason; Minneman, Michael P; Hoover, Erich; Weingast, Jessika; Ginner, Laurin; Leitgeb, Rainer; et al. (Journal of biomedical optics, 2016)
Studies have proven the relationship between cutaneous vasculature abnormalities and dermatological disorders, but to image vasculature noninvasively in vivo, advanced optical imaging techniques are required. In this study, we imaged a palm of a healthy volunteer and three subjects with cutaneous abnormalities with photoacoustic tomography (PAT) and optical coherence tomography with angiography extension (OCTA). Capillaries in the papillary dermis that are too small to be discerned with PAT are visualized with OCTA. From our results, we speculate that the PA signal from the palm is mostly from hemoglobin in capillaries rather than melanin, knowing that melanin concentration in volar skin is significantly smaller than that in other areas of the skin. We present for the first time OCTA images of capillaries along with the PAT images of the deeper vessels, demonstrating the complementary effective imaging depth range and the visualization capabilities of PAT and OCTA for imaging human skin in vivo. The proposed imaging system in this study could significantly improve treatment monitoring of dermatological diseases associated with cutaneous vasculature abnormalities.